Indoles mitigate the development of experimental autoimmune encephalomyelitis by induction of reciprocal differentiation of regulatory T cells and Th17 cells. (21st June 2013) - Rouse, Michael; Singh, Narendra P; Nagarkatti, Prakash S; Nagarkatti, Mitzi
<x xml:space="preserve">Abstract</x> Background and Purpose Dietary indole derivatives, indole‐3‐carbinol (I3C) and diindolylmethane (DIM), possess anti‐cancer properties and exhibit the characteristics of aryl hydrocarbon receptor (AhR) ligands. Because AhR activation has recently been shown to regulate T cell differentiation, we tested the hypothesis that I3C and DIM may mediate anti‐inflammatory properties by promoting regulatory T cell (T‐regs) differentiation while inhibiting Th17 cells. Experimental Approach We investigated the therapeutic efficacy of I3C and DIM against experimental autoimmune encephalomyelitis (EAE), a murine model of multiple sclerosis (MS). The efficacy was evaluated based on clinical scores of paralysis, histopathology, serum cytokines and infiltration of T cells in the CNS. We next studied the mechanism of induction of T cells against myelin oligodendrocyte glycoprotein (MOG35–55) peptide, both in vivo and in vitro, specifically investigating the differentiation of T‐regs and Th17 cells, and determined if indoles were acting through AhR. Key Results Pretreatment of EAE mice with I3C or DIM completely prevented the clinical symptoms and cellular infiltration into the CNS. Also, post‐treatment of EAE with I3C or DIM proved highly effective in curtailing the overall severity of the disease. In addition, I3C or DIM promoted the generation of T‐regs, while down‐regulating the induction of MOG‐specific Th17 cells. The regulation of FoxP3 induction and suppression of Th17 cells by indoles in vivo and in vitro were found to be AhR‐dependent. Conclusions and Implications Together, our studies demonstrate for the first time that I3C and DIM may serve as novel therapeutics to suppress neuroinflammation seen during MS through activation of AhR.